Executive decisions and operations research - Miller, David W.; Starr, Martin K. (Englewood Cliffs, N.J. : Prentice-Hall, 1969)
This book examines the structure of decision problems from the view point of an integrated theory of decisions. Within this framework, a logical, rational approach is blended together with the scientific methodology of operations research.
Includes index.
Includes bibliographical references: p. 589-594.
ne 02/03/2020
Loans
Keywords: Industrial management; Operations research